ANALISIS WEBSITE PENGELOLAAN DATA MENGGUNAKAN E-SUMUT PADA BAPPEDA SUMATERA UTARA - Qori Siagian; Darisma Daulay; Galang Desdwiansyah; Husein Nur Ansyari; Aidil Halim Lubis (UNIVERSITAS STEKOM, 2023)
This study aims to find out: Implementation of incoming and outgoing mail management, obstacles encountered in managing incoming and outgoing mail and efforts that can be made to improve management of incoming and outgoing mail at the Bappeda-Su office. Letters in the North Sumatra Regional Development Planning Agency (Bappeda) are still managed manually. To overcome this problem, we need an information system that can assist in archiving incoming and outgoing letters.